Implementation of Inpatient Medical Records at dr. Reksodiwiryo Hospital: A Qualitative Study: Pelaksanaan Rekam Medis Rawat Inap di Rumah Sakit dr Reksodiwiryo: Studi Kualitatif - Rahmi, Mutia; Sari, Ayulia; Siswati, Sri (JURNAL ILMU DAN TEKNOLOGI KESEHATAN TERPADU, 2023)
The objective of this study was to examine the implementation of medical records for hospitalized patients at dr. Reksodiwiryo Padang Hospital. The study employed a qualitative research methodology. Seven research informants were selected using the purposive sampling technique. Data were gathered through the utilization of in-depth interviews, on-site observations, and scrutiny of documents. The Miles and Huberman model was employed for data analysis, encompassing reduction, display, and conclusion operations. The data validity test employed both source triangulation and method triangulation. According to the research findings on the input element, the quantity of medical record personnel was adequate and there was an existing standard operating procedure (SOP). However, there was a lack of dedicated budget and insufficient facilities and infrastructure. The procedural element of patient documentation, particularly in regard to the recording of admission and discharge sheets, was not fully completed. There was a delay in the submission of medical records, resulting in suboptimal medical record processing. An error occurred during the medical record storage process, resulting in a misfile. The implementation of Medical Records for Inpatients at dr. Reksodiwiryo Padang Hospital was suboptimal and required enhancement. It is advisable for the hospital to provide training sessions to enhance the proficiency of medical record officers and familiarize them with the existing Standard Operating Procedures (SOPs).